Impact of Hepatitis C Virus Infection of Peripheral Blood Mononuclear Cells on the Immune System - Alhetheel, Abdulkarim Fahad (Frontiers in Virology, 2022)
Hepatitis C is a worldwide liver disease caused by hepatitis C virus (HCV) infection. The virus causes acute and chronic liver inflammation, and it is transmitted mainly by exposure to contaminated blood. HCV is capable of infecting hepatocytes and peripheral blood mononuclear cells, causing complications and disease progression. This mini review provides an overview of HCV infection, including details on the virological aspects, infection of the immune cells, and its impact on the immune system.